Ultrasonographic evaluation of urinary tract morbidity in school-aged and preschool-aged children infected with Schistosoma haematobium and its evolution after praziquantel treatment: A randomized controlled trial. - Beatrice Barda; Jean T Coulibaly; Christoph Hatz; Jennifer Keiser (PLOS Neglected Tropical Diseases, 2017)
BACKGROUND:Schistosoma haematobium infections are responsible for significant urinary tract (UT) complications. Schistosomiasis control programs aim to reduce morbidity, yet the extent of morbidity in preschool-aged children and the impact of treatment on morbidity reduction are not well studied. METHODOLOGY:Our study was embedded in a randomized, placebo-controlled, single-blind trial in Côte d'Ivoire, which evaluated the efficacy and safety of three doses (20, 40 and 60 mg/kg) of praziquantel in school-aged (SAC) and preschool-aged (PSAC) children infected with S. haematobium. Enrolled children were invited to participate in an ultrasound examination prior and six months after treatment. At these time points 3 urine samples were collected for parasitological and clinical examinations. PRINCIPAL FINDINGS:162 PSAC and 141 SAC participated in the ultrasound examination at baseline, of which 128 PSAC and 122 SAC were present at follow-up. At baseline 43% (70/162) of PSAC had UT morbidity, mostly at bladder level and 7% had hydronephrosis. 67% (94/141) of SAC revealed mainly moderate UT pathology, 4% presented pseudopolyps on the bladder wall, and 6% had pyelectasis. At follow up, 45% of PSAC and 58% of SAC were S. haematobium positive, mostly harboring light infection intensities (41% and 51%, respectively). Microhematuria was present in 33% of PSAC and 42% of SAC and leukocyturia in 53% and 40% of PSAC and SAC, respectively. 50% (64/128) of PSAC and 58% (71/122) of SAC presented urinary tract morbidity, which was mainly mild. A significant correlation (p<0.05) was observed between praziquantel treatment and reversal of S. haematobium induced morbidity. Progression of UT pathology decreased with increasing praziquantel dosages. A worsening of morbidity was observed among children in the placebo group. CONCLUSION/SIGNIFICANCE:Bladder morbidity is widespread among PSAC. Praziquantel treatment is significantly associated with the reversal of S. haematobium induced morbidity, which underscores the importance of ...